Pengaruh Gaya Hidup Konsumen terhadap Keputusan Pembelian Produk pada Informa Jambi Town Square Kota Jambi - Ahmad Tarmizi; Denny Asmas; Dimas Kurniawan (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
The purpose of this study is to analyze the influence of consumer lifestyle on purchasing decisions at Informa Jambi Town Square in Jambi City. The approach used was a quantitative method with a simple linear regression model. Questionnaires were distributed to a sample of 95 respondents. The results indicate that lifestyle variables have a positive and significant effect on purchasing decisions at Informa Jambi Town Square in Jambi City.